Computational Analysis of Epstein-Barr Virus BamHI A Rightward Transcript (BART) MicroRNAs (miRNAs) Regulation on Messenger RNAs and Long Non-Coding RNAs in Nasopharyngeal Cancer: Epstein-Barr Virus Regulation on ceRNA Network - SADAI, DAPHNE OLIVIA JAWAI; SIM, EDMUND UI HANG (Borneo Journal of Resource Science and Technology, 2024)
To date, the regulatory framework mediated by Epstein-Barr virus (EBV) BamHI A rightward transcript (BART) microRNAs (miRNAs) via their interaction with long non-coding RNAs (lncRNAs) in the context of nasopharyngeal cancer (NPC) pathogenesis remains partially understood. To derive a more complete insight into this phenomenon, we embarked on a computational study to identify BART miRNAs, mRNAs, lncRNAs, and all associated factors relevant to NPC tumourigenesis and to characterise their interactions. In silico integration of multi-level RNA expression and construction of regulatory networks were performed. We found six EBV BART miRNAs (ebv-miR-BART21-3p, ebv-miR-BART19-3p, ebv-miR-BART15, ebv-miR-BART2-5p, ebv-miR-BART20-3p and ebv-miR-BART11-5p) that could interact with four mRNAs (EYA4, EYA1, EBF1 and MACROD2) associated with NPC pathogenesis. These mRNAs can interact with six non-EBV miRNAs (hsa-miR-1246, hsa-miR-93-5p, hsa-miR-16-5p, hsa-miR-135b-5p, hsa-miR-211-5p and hsa-miR-1305), which in turn, could interact with three lncRNAs (CASC2, TPTE2P1 and ARHGEF26-AS1). These findings could shed light on the roles of dysregulated competing endogenous RNA (ceRNA) network in NPC oncogenesis. In addition, we have also predicted the oncogenic and tumour suppressive functions of BART miRNAs and lncRNAs, and more precisely, the involvement of BART miRNAs in DNA repair regulation and apoptosis.